Unveiling the silent threat among us: leveraging health information technology in the search for asymptomatic COVID 19 healthcare workers. (9th November 2020) - McKeeby, Jon W; Siwy, Christopher M; Revoir, Josanne; Carlson, Seth D; Joyce, Maria D; Bailin, Heike; Frank, Karen M; Krumlauf, Mike; Matlock, Ann Marie; Lee, Laura M; Sparks, Mary; Barnes, Tony; et al.
Abstract: Assuring the safety of both patients and healthcare workers (HCWs) in hospitals has been the primary focus of every healthcare organization during the COVID 19 pandemic. This article discusses the NIH Clinical Center's interdisciplinary approach to deploying an organizational Asymptomatic Staff Testing System.